Pemanfaatan Limbah Kulit Tiram Sebagai Substitusi Semen pada Campuran Bata Ringan - Saddam Saktya Sandytia; Tommi Akbar Prasetyo; Shifa Fauziyah; Hartono Hartono (Jurnal Sipil dan Arsitektur, 2024)
Indonesian coastal areas of tourist spots that cause large amounts of seafood waste, such as oyster shells, led to the idea of reducing beach pollution by using oyster shells as a partial substitute for lightweight bricks as construction material. Lightweight bricks require high costs and have a heavy mass as walls, so oyster shell powder, which contains calcium carbonate and has a smaller specific gravity, is expected to qualify the Indonesian National Standard (SNI) requirements for lightweight bricks. The research method is quantitative experimental, which observes the effect of variables based on SNI. The composite of the lightweight brick combination is 0.35 Water Cement Ratio (FAS): 1 cement: 2 sand: 1 foam agent: 50 water, and the variable of oyster shell powder added to the cement is 0%, 3%, 6%, 9%, and 12% of cement. The quality test for oyster shell powder for making lightweight bricks based on SNI 8640, 2018, includes density, water absorption (porosity), and compressive strength tests. The result of average density analysis for 0% = 986 kg/m³, 3% = 954 kg/m³, 6% = 978 kg/m³, 9% = 920 kg/m³, and 12% = 903 kg /m³.  According to the Indonesian National Standard (SNI), the porosity test results maximum is 25%, the result of average porosity analysis at 0% = 21.2%, 3% = 19.2%, 6%  = 17.2%, 9%  = 23%, and 12% = 24.6%. Compressive strength analysis results at 0%  = 2.3 MPa, 3% = 1.9 MPa, 6%  = 2.1 MPa, 9% = 1.7 MPa, and 12%  = 1.6 MPa. In conclusion, oyster shell powder waste can reduce density, reduce porosity to the optimum point, increase the porosity afterward, increase compressive strength to the optimum point, and reduce compressive strength after passing the optimum point.